Development landscape language as tourist attraction in the area destination tour Regency Humbang Hasundutan - Selli, Selli; Sibarani, Robert; Rujiman, Rujiman; Siagian, Morida (International Conference on Sciences Development and Technology, 2022)
Developing landscape language is something effort important in strengthen identity culture something area destination tour. Regency Humbang Hasundutan, a region in Indonesia which is rich in diversity culture and nature, have potency big for developed become objective interesting tour. However, one necessary aspect noticed in development destination tour is diversity language in the area the Study This aim for analyze and identify diversity language in the District Humbang Hasundutan as well as develop a development strategy landscape language that can support development destination tour. Method study This using interactive models in form qualitative. Research results found: first, still There is object tours in the area destination tour Regency Humbang Hasundutan yet complete landscape language so that lack of information landscape object language tour the. Development landscape language need be equipped start from landscape language Happy come to tourist are, landscape language pointer direction to location object travel, landscape language Happy comeacross the object travel, landscape language folk and landscape discourse language description empirical or geographic with implement this strategy, it is expected Regency Humbang incitement can maintain and develop diversity language as assetvaluable culture. Development landscape strong language will give contribution positive for development destination travel, increase Power pull travel and deliver experience different to visitor. Besides that, development landscape language willgive benefit social, like strengthen identity culture public local and push participation public in development tourist in a manner sustainable.